Osteosarcopenia: key molecular mechanisms and translational perspectives - Pu, Yuan; Teng, Yirong; Li, Yinghua; Zhou, Yunchun; Gao, Ming; Yan, Zilin; Teng, Zhaowei (Frontiers in Physiology, 2026)
The coexistence of osteoporosis and sarcopenia is recognized as a syndrome known as osteosarcopenia. As an aging-related disease, research into the molecular mechanisms of osteosarcopenia has gradually shifted from the study of single-organ pathology to the elucidation of multidimensional interactions. This review aims to construct a hierarchical framework of “intracellular - intercellular - systemic” to systematically elaborate on the pathogenesis of osteosarcopenia. Based on this foundation, it explores frontier interventions and their prospects for clinical transformation, including bone-targeting F6-(DSS)6-exo nanoparticles, miR-495, natural active compounds (resveratrol, nuciferine), Clostridium butyricum, and bimagrumab. Future research should focus on analyzing the microenvironment of the musculoskeletal interface, utilizing deep learning CT analysis for early risk identification, and exploring the application of biomaterials in osteomuscular regeneration. This review aims to provide a reference for the field of mechanism research in osteosarcopenia and offer new insights for its precision prevention and treatment.